Intermittent water supply and self-rated health in rural China's karst region - Wu, Guoyong; Cheng, Jianwei; Yang, Fan; Riaz, Noman (Frontiers in Public Health, 2023)
Introduction With rapid economic and social development, surging demand for domestic water, and the increasing shortage of water resources, the applications of intermittent water supply systems have become more common in rural China and other developing countries. The accompanying hygiene risks require our more attention. Methods Based on the Grossman model, this paper conducted an IV-Oprobit model to investigate whether and how intermittent water supply affect rural residents' self-rated health status. Our data came from “China Karst Rural Economic Survey (CKRS)”, which covers 8 provinces and 641 villages in rural China's karst region. Results and discussion We found that: (1) Intermittent water supply has adverse effects on the self-rated health status of rural residents. Compared with the rural residents under continuous water supply, the probability of “fair” health status under intermittent water supply significantly increases by 18.2%, while the probability of “excellent” significantly reduces by 58.8%. (2) Residents' water storage behavior and sanitary water habit are important mechanisms for intermittent water supply to affect residents' self-rated health status; (3) Intermittent water supply has a greater impact on the self-rated health of females and the groups with lower education levels. The results of our study have the following policy implications: relevant departments should make a rational plan about water supply methods and improve related supporting measures; we should strengthen health education for rural residents on water behavior to standardize their water storage and sanitary water behavior; government should enhance the pertinence of policy implementation and favor specific measures to specific populations.